A quick screening to assess the phytoextraction potential of cadmium and copper in Quercus pubescens plantlets - Di Santo P; Cocozza C; Tognetti R; Palumbo G; Iorio ED; Paura B (iForest - Biogeosciences and Forestry, 2017)
The relevance of the environmental pollution by heavy metals warrants the necessity to develop and assess more efficient plant-based technologies. This study was conducted to evaluate a quick screening approach in order to investigate the cadmium (Cd) and copper (Cu) phytoextraction potential of Quercus pubescens in a micro-propagation system. Increasing concentrations of Cd (0, 5, 50, and 250 µM) and Cu (0, 5, 50, 250 and 500 µM) were separately applied to evaluate the effect of metals on their absorption and accumulation in downy oak plants. At high concentrations, Cd and Cu significantly reduced the dry biomass of shoots and roots and the plant tolerance index. Cd was toxic at increasing concentrations, inducing higher reduction of shoot dry mass than roots, whereas Cu increased dry mass at 5 µM. This study represents the first attempt to assess Cd and Cu uptake in Q. pubescens under in vitro conditions. The in vitro screening potential is meanly related to the following purposes: (i) proper selection of plant materials resilient to excess metals in the growth substrate; (ii) efficient removal of metals by the selected tree species; (iii) minor interference with the growth of plants accumulating metals in their tissues; (iv) rapid provision of plant materials for tree breeding programs.